The Effect of Blended Learning Model towards Students’ Writing Ability - Wahyuni, Sri (J-SHMIC, 2018)
The rapid development of science and technology in the current era of globalization brings many changes in various aspects of social life. These changes include education. Recognizing this, Indonesia has published English as one of the crucial subject. However, students got some difficulties in writing. To assist students in solving writing problem, this study was conducted to know the effect of blended learning model towards students’ writing ability of the eleventh grade students at SMAN 6 Pekanbaru. Sample of the study was determined through random sampling method. There were 10 classes randomly selected. It consisted of two classes that were XI IPA 1 as experimental class and XI IPA 2 as control class. Afterwards, the experimental group was taught by applying blended learning model through Telegram Messenger and the control group was instructed through the traditional method by lecturing method. To gain data, writing test was administered. After collecting data, the mean scores of the pre-test and the post-test for the two groups were calculated using the t-test. Findings of the study revealed that there were  statistically significant  differences  between  the  means  of  two  groups  in  favor  of  the experimental group which achieved better results in the post-test. It was proved by the significant level of  0.05 which was t=3.983 and p=0.000. On the other hand, there is a significant effect of blended learning model towards students’ writing ability.